ANALISIS YURIDIS PIDANA MATI TERHADAP TINDAK PIDANA NARKOTIKA (ANALISIS PUTUSAN NOMOR 2267/PID.SUS/2012/PN.JKT.BAR) - Wahyu Pambudi, Arif; Zein Sgn, Subhan (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
The crime committed by Fredi Budiman was a very extraordinary crime in narcotics crimes. Therefore, it is very interesting and important to examine further how the perpetrators who are suspected of being narcotics dealers are proven in decision number 2267/Pid.Sus/2012/PN.Jkt.Bar? and what is the juridical analysis of the death penalty for narcotics crimes in decision number 2267/ Pid.Sus/2012/PN.Jkt.Bar?. To answer these problems, normative juridical legal research methods are used with statutory and conceptual regulatory approaches. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results, it was found that valid evidence according to Law Number 8 of 1981 is regulated in Article 184 of the Criminal Procedure Code which consists of: a) witness statements; b) expert testimony; c) letter; d) instructions and d) defendant's statement. Based on the decision in case Number 2267/PID.SUS/2012/PN.JKT.BAR. There are three valid pieces of evidence, namely witness statements, documentary statements, and defendant statements. The execution of the death penalty for narcotics crimes in Law No. 35 of 2009 concerning Narcotics is the heaviest sanction that can be imposed on perpetrators of this type of crime. Basically, the death penalty imposed on narcotics traffickers is a form of protecting the rights and interests of many people and is in line with the purpose of punishment. The reason for the punishment of repetition as a basis for increasing punishment is that someone who has been sentenced and repeats a crime again, proves that he has a bad character. Evil is therefore considered very dangerous for security and public order.